Pre-diagnosis and pre-treatment loss to follow-up and associated factors among patients with presumed tuberculosis and those diagnosed in Uganda - Rebecca Nuwematsiko; Noah Kiwanuka; Solomon T. Wafula; Mary Nakafeero; Lydia Nakanjako; Henry Luzze; Stavia Turyahabwe; Juliet N. Sekandi; Lynn Atuyambe; Esther Buregyeya (BMC Health Services Research)
Abstract Background Loss to follow-up (LTFU) of patients with presumed tuberculosis (TB) before completing the diagnostic process (pre-diagnosis LTFU) and before initiating treatment for those diagnosed (pre-treatment LTFU) is a challenge in the realization of the End TB Strategy. We assessed the proportion of pre-diagnosis and pre-treatment LTFU and associated factors among patients with presumed TB and those diagnosed in the selected health facilities. Methods This was a retrospective cohort study involving a review of routinely collected data from presumptive, laboratory and TB treatment registers from January 2019 to December 2022. The study was conducted in three general hospitals and one lower-level health center IV in Central Uganda. We defined pre-diagnosis LTFU as failure to test for TB and obtain results within 30 days from the date of being presumed and pre-treatment LTFU as failure to initiate TB treatment within 14 days from the date of diagnosis. Modified Poisson regression was used to estimate prevalence ratios (PRs) and 95% confidence intervals (CIs) of factors associated with pre-diagnosis and pre-treatment LTFU. Results Of the 13,064 patients with presumed TB, 39.9% were aged 25 to 44 years, and 57.1% were females. Almost a third, 28.3% (3,699/13.064) experienced pre-diagnosis LTFU and 13.7% (163/1187) did not initiate treatment within 14 days from being diagnosed. Pre-diagnosis LTFU was more likely to occur among patients aged 0-14 years (adj PR 1.1, 95% CI: 1.06,1.24), females (adj.PR=1.06, 95% CI: 1.01, 1.12) and those with no record of place of residence (adj. PR=2.7, 95% CI: 2.54, 2.93). In addition, patients with no record of phone contact were more likely to be LTFU, (adj. PR=1.1, 95% CI: 1.05, 1.17). Pre-treatment LTFU was also more likely among patients with no record of place of residence (adj PR 7.1, 95% CI: 5.13,9.85) and those with no record of phone contact (adj PR 2.2, 95% CI: 1.63,2.86). Patients presumed from the HIV clinics were 40% less likely to experience pre-treatment LTFU compared to those in the outpatient departments (adj PR 0.6, 95% CI: 0.41,0.88). Conclusion High proportions of pre-diagnosis and pre-treatment LTFU were observed in this study. This calls for urgent interventions at these time points in the TB care cascade to be able to realise the End TB Strategy.